Are ivory antiques actually antique? - Kufnerová, Jitka (Crime, law and social change, 2021)
Twenty-five samples of ivory artefacts were analysed using a radiocarbon dating method. These artefacts were part of a collection of 77 items seized during a wildlife law enforcement operation targeting online illegal ivory trade. Based on the opinion of a qualified expert, 14 of the 25 samples were declared antique, meaning their presumed origin is older than 1947. According to the European Union’s law, antique ivory is exempt from an otherwise total ban on commercial ivory activities since such trade does not contribute to the current decline in elephant population. The radiocarbon measurement has revealed alarming findings that 17 of the 25 processed samples (68%) are not antique as their origin is younger than 1947. The antique expert’s determination of the ivory age failed in 12 of 14 cases (86%).